Paradoxical reactions during tuberculosis treatment in patients with and without HIV co-infection. Issue 8 (28th July 2004) - Breen, R A M; Smith, C J; Bettinson, H; Dart, S; Bannister, B; Johnson, M A; Lipman, M C I
Abstract : Background: It has been suggested that deterioration of tuberculosis (TB) during appropriate treatment, termed a paradoxical reaction (PR), is more common and severe in HIV positive individuals on highly active antiretroviral therapy (HAART). Method: A study was undertaken to determine the frequency of PR and its associated features in a population of HIV+TB+ patients and a similar sized group of HIV−TB+ individuals. Results: PR occurred in 28% of 50 HIV+TB+ patients and 10% of 50 HIV−TB+ patients. Disseminated TB was present in eight of 13 HIV+TB+ patients and four of five HIV−TB+ patients with PR. In 28 HIV+TB+ patients starting HAART, PR was significantly associated with commencing HAART within 6 weeks of starting antituberculosis treatment (p = 0.03) and was more common in those with disseminated TB (p = 0.09). No association was found between development of PR and baseline CD4 count or CD4 response to HAART. Conclusions: PR is common in HIV infected and uninfected individuals with TB. Early introduction of HAART and the presence of disseminated TB appear to be important in co-infected patients.